RESILIENSI : Kemampuan Beradaptasi Dan Bertahan Dalam Menghadapi Tantangan Hidup Yang Sulit - Ayu Hayati Lubis; Firman; Netrawati (CV. ITTC INDONESIA, 2024)
Resilience refers to the ability of an individual or group to adapt, survive, and bounce back from difficult or challenging situations. In a world full of uncertainty, resilience becomes a very important quality to ensure survival and mental well-being. This article discusses the concept of resilience as the ability to manage stress, overcome adversity, and adapt to change, both on an individual and social scale. Resilience is not only related to physical or mental strength, but also to external factors such as social support, a supportive environment, and the capacity for positive thinking. In a social context, resilience also involves the capacity to work together, build support networks, and develop skills that can help individuals and groups to remain strong in the face of crisis.